Women''s Fiction 1945-2005 : Writing Romance. - Philips, Deborah (Continuum literary studies., 2007)
Organised around each decade of the post war period, this book analyses novels written by and for women from 1945 to the present. Each chapter identifies a specific genre in popular fiction for women which marked that period and provides case studies focusing on writers and texts which enjoyed a wide readership. Despite their popularity, these novels remain largely outside the ''canon'' of women''s writing, and are often unacknowledged by feminist literary criticism. However, these texts clearly touched a nerve with a largely female readership, and so offer a means of charting the changes in i.